Electromagnetic field effects on the kinetics of solid-state reduction of iron oxides with gases - Grishin , O.M.; Velychko , O.G.; Grek , O.S.; Nadtochii , A.A. (Theory and Practice of Metallurgy, 2025)
Objective. The aim of the work is to study the physicochemical correlations of the intensifying effect of an electromagnetic field on the process of solid-phase reduction of oxides by gases. Methods. The experiments were carried out in an alternating magnetic field with an alternating current frequency in the inductor up to 40 kHz using the thermogravimetric technique. The process of indirect reduction was studied to determine the degree and rate of oxide reduction in the temperature range of 973-1373 K using various iron ore materials. Results. The results of laboratory experiments indicate the influence of a high-frequency intensifying electromagnetic field on the process of solid-phase reduction of iron ore materials. A physicochemical model of the mechanism of the intensifying effect of EMF on the reduction process is presented. The high-frequency field significantly accelerates the diffusion processes and increases the electronic and structural defectiveness of the crystal lattice, which positively influenced the development of the adsorption-chemical link. Scientific novelty. The effect of EMF on the kinetics of gas reduction of iron ore materials has been experimentally confirmed. Practical significance. The intensification of solid-phase reduction of iron ore raw materials leads to the intensification of the process and increase of the process productivity.